Assessing ethno-veterinary practices in Kashmir Himalayas: Traditional knowledge and its role in animal healthcare - Abrar Y. MIR; Muzafar RIYAZ; S. IGNACIMUTHU (Nova Geodesia, 2023)
This study was aimed at exploring the ethno-veterinary practices in the District of Kupwara in Jammu and Kashmir Union Territory of India, by examining the traditional knowledge and its application in animal healthcare. The study included qualitative methods, such as interviews with local farmers (n=100) and traditional healers, as well as observation of their practices from February to April 2023. The results revealed a rich knowledge base among the local community regarding the use of medicinal plants for treating a range of animal ailments. 32 plants of pharmaceutical value representing 23 families have been assessed, with the Asteraceae family receiving the greatest attention. Eighty-eight percent of these ethnoveterinary medicinal plant species were herbs. Leaves of these plants were used most often (27%), followed by the entire plant (21%), seeds (21%), roots and fruits (9%), bulbs (6%), and stems and rhizomes (3%). Glycine max (0.91) and Allium sativum (UVi = 0.89) had the highest UVi values, whereas Oryza sativa (0.51), Allium sativum (0.49), and Zea mays (0.43) were the most cited and most often mentioned therapeutic plant species. Traditional veterinary practices were found to be deeply embedded in the local culture and were passed down through generations of farmers and traditional healers. These practices are still widely used today, in combination with modern veterinary medicine, to provide comprehensive care to livestock in the region. This study highlights the importance of preserving and promoting ethno-veterinary knowledge and practices as a valuable resource for animal healthcare in rural communities.